Simulation of Opening Angle of Archimedes Wind Turbine Design Based on the Fibonacci Series - Herraprastanti, Eva; Agung Saputro, Widianto (International Journal of Engineering, Science and Information Technology, 2022)
The configuration of new type of turbine is the Archimedes wind turbine with a spiral structure whose design is inspired by logarithmic spirals. This type of wind turbine uses lift and drag to harness the kinetic energy of the wind. The eccentric design has aerodynamic characteristics that have been the focus of previous research. The design is made from the arrangement of the Fibonacci sequence (1x1, 2x2, 3x3, 5x5, 8x8) or commonly known as the golden ratio. This study aims to analyze the coefficient of lift (CL) and coefficient of drag (CD) with variations opening angle of 35°, 45°, 65°, air fluid, turbulent flow, Re 1200, pressure distribution 1 atm, wind speed 5, 5 and 15 m/s. The results is at wind speed of 5.5 m/s, an angle of 35°, the CL value is 1.07E+02, the CD value is 4.02E+04. At wind speed of 5.5 m/s, an angle of 45°, the CL value is 1.08E+04, the CD value is 1.77E+01. At wind speed  of 5.5 m/s, an angle of 65°, the CL value is 1.84E+06, the CD value is 3.68E+04. At wind speed  of 15 m/s, an angle of 35°, the CL value is 2.20E+03, the CD value is 9.76E+02. At wind speed  of 15 m/s, an angle of 45°, the CL value is 5.51E+04, the CD value is 4.12E+02. At wind speed  of 15 m/s, an angle of 65°, the CL value is 5.96E+01, the CD value is 1.33E+03. Based on this, it can be concluded that at wind speed  of 5.5 m/s the higher the opening angle, the higher CL produced. At wind speed  of 15 m/s the larger the opening angle the CD increases. This is because the higher the angle, the more it receives sweeps or catches the wind. While the unstable value generated in this simulation is generally a weakness in the wind turbine design.